If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7b + 3 = 5b + -11 Reorder the terms: 3 + 7b = 5b + -11 Reorder the terms: 3 + 7b = -11 + 5b Solving 3 + 7b = -11 + 5b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5b' to each side of the equation. 3 + 7b + -5b = -11 + 5b + -5b Combine like terms: 7b + -5b = 2b 3 + 2b = -11 + 5b + -5b Combine like terms: 5b + -5b = 0 3 + 2b = -11 + 0 3 + 2b = -11 Add '-3' to each side of the equation. 3 + -3 + 2b = -11 + -3 Combine like terms: 3 + -3 = 0 0 + 2b = -11 + -3 2b = -11 + -3 Combine like terms: -11 + -3 = -14 2b = -14 Divide each side by '2'. b = -7 Simplifying b = -7
| -6+6x+7=(x+1)-2 | | -40-8=6s | | -2=0-1/5j | | 9-5a+a=-3 | | 6n-7(n-1)=12 | | 2m+6=2m-2 | | 5(z+6)=2+3z | | (6/5(p-4))-(6/5p) | | 0=16t^2+138t+55 | | 6a+2a+12=7+6a+3 | | 4x-5+2x=13 | | y=4x^2-6x-7 | | 0=16t^2+138t+c | | x^2-y^2=50 | | x+8+5x=2-2x | | 2x^3+7x^2-15=0 | | 7.6x-1.6=13.6 | | 2k=56 | | m-7m+6=20 | | -5k+3=-6+4k | | 6(k-3)-7=6k-(5k-2) | | x^2-x^2-2+1=7 | | 55r^2+28r-3= | | -y-2=11 | | 2(7x+3)+4=7(2x-1)+2x | | 7y/12-5=9-4y/3 | | 8+4=2(x-12) | | -70-2.25x=182.50 | | 2138=n+38 | | 10x+20xy+7y=100 | | 3x-7=2(x-4)+15 | | 7u-5u=-43 |